Hubungan Kegiatan Ekstrakurikuler Pramuka dengan Prestasi Belajar Siswa di SMA N X Koto Singkarak - Oki Saputra; Hadiyanto Hadiyanto; Ahmad Sabandi; Lusi Susanti (Universitas Negeri Padang, 2021)
Abstract This reseach is the meaning to get information on the relationship of scout ectrakurikular activities to student achievement in SMA N 1 X Koto Singkarak. The purposed of this studi is to obtan informaton on: 1) Student achievement, 2) Scout extracurricular activities and 3) The relationship of Scout extracurricular activities to student learning achievement. The populati in this studi is the whole student who follows the extracurricular scouts in SMAN 1 X Koto Singkarak amounted to 228 people. The sample in this studi amouted to 66 peoples using the Slovin formula and take with proportonal stratfied random sampling techniq. The reseach instrumen use is questionaire using the Likertscale model with 5 answers the answers that have been teste validitiy and reliabilitiy by using SPSS version 16.0. Data analyze usng product moment corelation formula. The result of data analysis show 1) the achievement of low-category student's study is 67.8% 2) Excillant activity of scouting category is quite good 73% and 3) There is a significant relationshipp between scout extracurricular activities on student achievement in SMAN 1 X Koto Singkarak R hitung at 0.728> R tabel 0.24 and Thacung value 8,495> Ttable 1.980 at the level of confidence 95% of this study showed that there is a mean relationship on the scout extracurricular activities to student achievement at SMAN 1 X Koto Singkarak. This means that the scout extracuricular activites are one of the factor that affect student achievement in SMAN 1 x Koto Singkarak.